Design early phase drug combination trials: methods - Yuan, Ying (Henry Stewart Talks, 2017)
Challenges of drug combination trials, Phase I combination trial designs for finding a single MTD, Linearization approach, BOIN design, Phase I combination trial design for finding the MTD contour, Waterfall design